2022
DOI: 10.1134/s2079057022040063
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Complications and Consequences of the Novel Coronavirus COVID-19 Infection in Elderly and Senile Patients (Literature Review)

Abstract: Based on available publications, the article systematizes information about some forms of lesions of the central nervous system (CNS), their pathogenesis and clinical manifestations in the case of COVID-19. The risk factors, mechanisms of development, diagnostic approach, and the age characteristics of patients with neurological complications of COVID-19 are discussed. The specific mechanisms of the neuroinvasiveness and neurovirulence of the SARS-CoV-2 virus, regardless of the age of patients and the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Based upon the above findings, Heneka et al [ 458 ] posited that NLRP3 inflammasome activation during COVID-19 heightens the risk for the later development of chronic neurodegenerative diseases. Independent clinical and epidemiological investigations indicated that SARS-CoV-2 infection and the ensuing “long COVID” tightly relate to the onset of AD, PD, prion disease (PrD), and other ailments, particularly in patients in advanced age or suffering from intercurrent illnesses (CVD, T2DM, hypertension, other neurological disorders) or severe/fatal COVID-19 [ 459 , 460 , 461 ]. Even more alarming, the receptor-binding domain of SARS-CoV-2’s S1 spike glycoprotein presents prion-like sequences.…”
Section: Brain Nlrp3 and Neurotropic Viruses Infectionsmentioning
confidence: 99%
“…Based upon the above findings, Heneka et al [ 458 ] posited that NLRP3 inflammasome activation during COVID-19 heightens the risk for the later development of chronic neurodegenerative diseases. Independent clinical and epidemiological investigations indicated that SARS-CoV-2 infection and the ensuing “long COVID” tightly relate to the onset of AD, PD, prion disease (PrD), and other ailments, particularly in patients in advanced age or suffering from intercurrent illnesses (CVD, T2DM, hypertension, other neurological disorders) or severe/fatal COVID-19 [ 459 , 460 , 461 ]. Even more alarming, the receptor-binding domain of SARS-CoV-2’s S1 spike glycoprotein presents prion-like sequences.…”
Section: Brain Nlrp3 and Neurotropic Viruses Infectionsmentioning
confidence: 99%